SCHOOL-BASED POLICY MANAGEMENT: IMPLEMENTATION OF AN APPROACH TO POLICY MANAGEMENT - Anisa, Zahro (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
School-Based Policy Management (MKBS) provides autonomy to schools to formulate and implement policies according to local needs. Therefore, the aim of School-Based Policy Management (MKBS) is to improve the quality of education and school effectiveness by providing autonomy to educational institutions. The research method used is a qualitative case study type method. To get an overview of the policies that are managed, researchers conducted direct observations and documented how policy management occurred at the MTS Nurul Jadid school. The results of the research show that the implementation of policy management that occurs at MTS Nurul Jadid is through the policy implementation model according to Van Meter and Van Horn in offering a basic model with six variables that form a linkage between policy and performance, namely: basic measures and policy objectives, policy sources, communication between organizations and implementation activities, characteristics of implementing agencies, economic, social and political conditions, tendencies of implementers. This research has the implication that policy management that is carried out well can support student development, teacher discipline and can manage schools to be of higher quality.